Impact of brain‐derived neurotrophic factor genetic polymorphism on cognition: A systematic review - Toh, Yi Long; Ng, Terence; Tan, Megan; Tan, Azrina; Chan, Alexandre (Brain and behavior, 2018)
Introduction Brain‐derived neurotrophic factor (BDNF) has an important role in the neurogenesis and neuroplasticity of the brain. This systematic review was designed to examine the association between BDNF Val66Met (rs6265) polymorphism and four cognitive domains—attention and concentration, executive function, verbal fluency, and memory, respectively. Methodology Primary literature search was performed using search engines such as PubMed and Scopus. Observational studies that evaluated the neurocognitive performances in relation to BDNF polymorphism within human subjects were included in this review, while animal studies, overlapping studies, and meta‐analysis were excluded. Results Forty of 82 reviewed studies (48.8%) reported an association between Val66Met polymorphism and neurocognitive domains. The proportion of the studies showing positive findings in cognitive performances between Val/Val homozygotes and Met carriers was comparable, at 30.5% and 18.3%, respectively. The highest percentage of positive association between Val66Met polymorphism and neurocognition was reported under the memory domain, with 26 of 63 studies (41.3%), followed by 18 of 47 studies (38.3%) under the executive function domain and four of 23 studies (17.4%) under the attention and concentration domain. There were no studies showing an association between Val66Met polymorphism and verbal fluency. In particular, Val/Val homozygotes performed better in tasks related to the memory domain, while Met carriers performed better in terms of executive function, in both healthy individuals and clinical populations. Conclusion While numerous studies report an association between Val66Met polymorphism and neurocognitive changes in executive function and memory domains, the effect of Met allele has not been clearly established. A total of 82 relevant studies were reviewed. The proportion of the studies which showed positive findings in cognitive performances between Val/Val homozygotes and Met carriers was comparable, at 30.4% and 18.2%, respectively. Our findings showed that the highest percentage of positive association between Val66Met polymorphism and neurocognition was reported under the memory domain; with 26 of 63 studies (41.3%) followed by 18 of 47 studies (38.3%) under executive function domain and four of 23 studies (17.4%) under attention and concentration domain.